Innovation economics - the leading economic doctrine for Science and Technology to become the driving force of economic development in the 21th century - Quan, Nguyen Manh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
The second half of the 20th century has seen the remarkable contributions of R&D which create the exceptional economic growth of USA, Western Europe, Japan and other new industrialized countries (NIC). The same time, particularly after the world crisis at the end of the century we have seen the great fluctuations of the world economy partially caused by the role of S&T. The dual impacts, positive and negative, of the historical role of S&T in the economic growth of this period are reflected through the evolution of the economic doctrines governing the economic and S&T policies of the world great economies, such as the US one during the late end of the 20th century. Some new economic doctrines emerged, namely the Neo-classical economics, Neo-Keynes economics and, most recently, the Innovation economics. This paper would summarize the main features of the above mentioned economic doctrines and show out the important remarks for Vietnam in application of the approaching concepts by the Innovation economics for our problems of macro-economic policies. Here we will find some “traces’ of the Neo-classical economics and the Neo-Keynes economics very distant from the approaching concepts of the Innovation economics. Code: 11060201